Esthetic Smile Perception Among Dental Students at Different Educational Levels - Althagafi N (Dove Medical Press, 2021)
Nebras Althagafi Department of Pediatric Dentistry and Orthodontics, College of Dentistry, Taibah University, AlMadinah AlMunawwarah, 42353, Saudi ArabiaCorrespondence: Nebras Althagafi Tel +966-564060607Email althagafi.nebras@gmail.comPurpose: To evaluate the perception of six esthetic components of the smile among dental students and whether such a perception was influenced by different education levels and gender.Materials and Methods: This was an analytical cross-sectional study. A self-administered questionnaire was applied to all students (n=182) at clinical levels (year four and five) to evaluate a total of 6 ideal images (smile arc [SA], buccal corridor [BC], gingival display [GD], midline diastema [MD], crown length [CL] and width [CW]). In addition, students were asked to evaluate 20 altered images of these ideal images. A 10-point visual analogue scale was used to assess the ideal images, with the right end of the scale labeled “attractive smile” and represented by the number 10 and the left end of the scale labeled “unattractive smile” and represented by the number 0. The opposite scoring was applied for the altered esthetics smile images. Descriptive statistics was run to report sample characteristics, and the Mann-Whitney U-tests were performed to compare clinical levels and gender on aspects of esthetic smile.Results: The response rate was 80% (77 females and 68 males). Students at level five scored statistically significantly (p< 0.001) higher towered attractive esthetic smile in ideal SA, while students at level four scored statistically significantly (p=0.016 and 0.006, respectively) higher towered attractive esthetic smile in ideal GD and CL. At altered smile esthetics images evaluation, fifth year dental students scored statistically significantly (p=0.030, 0.026 and 0.028, respectively) higher towered unattractive esthetic smile in two altered images of SA and one of BC. In contrast, fourth year dental students scored statistically significantly (p=0.022, 0.048, 0.027, respectively) higher towered unattractive esthetic smile in one altered image of GD, midline diastema and crown width. Males in year four were more likely to score higher than females for ideal images meanwhile females in year five scored higher than males towards attractive smile in ideal images. Males and females differences in scoring ideal images on both levels were generally non-significant (P> 0.05) although males were statistically significantly to score higher than females towards unattractive images in both levels (p< 0.05).Conclusion: Dental students at the fifth-year level of study had higher perception of esthetic components of smile than those at the fourth-year level. At each level of study, female dental students apparently had higher perceptions of smile esthetics than males.Keywords: dentistry, orthodontics, smile, beauty, dental students, perception, gender differences